Ability of Pediatric Emergency Medicine Physicians to Identify Anatomic Landmarks With the Assistance of Ultrasound Prior to Lumbar Puncture in a Simulated Obese Model. Issue 1 (January 2015) - Restrepo, Christopher G.; Baker, Mark D.; Pruitt, Christopher M.; Gullett, John P.; Pigott, David C.
Abstract : Objectives: Lumbar punctures (LPs) are typically performed using anatomical surface landmarks. However, as body mass index increases, identifying surface landmarks becomes more difficult. Ultrasound has been proposed as a tool for identifying these landmarks prior to LP. This study evaluates the effectiveness of a brief training program in ultrasound identification of anatomical landmarks in a simulated obese model prior to completing an LP. Methods: Pediatric emergency medicine physicians completed a pretest questionnaire on ultrasound familiarity prior to an educational session. Participants utilized ultrasonography without the assistance of palpation on a simulation LP model saving images for review. Participants attempted LP on phantom models with simulated body mass indices of 35 and 40 kg/m 2 . Time to image acquisition and successful aspiration of cerebrospinal fluid from the model were recorded. Two expert sonologists independently reviewed all images for correct landmark identification. Results: Seven of the 19 participants had previous familiarity with ultrasound. The mean time to lumbar image acquisition significantly improved for all individuals from 176 seconds to 100 seconds ( P = 0.003). Comfort level with ultrasound improved ( P < 0.001) as well as comfort level in performing a lumbar ultrasound ( P < 0.001). Adequate images were obtained in 96% of the attempts (55/57). The success rate at performing LP was 95% (54/57). Conclusions: After a brief education intervention, pediatric emergency medicine physicians with little to no previous training in ultrasound can obtain adequate lumbar anatomic images and successfully perform LP in a simulated obese model. Comfort level with ultrasound significantly improves with a short course in ultrasound fundamentals.